The Authority of Local Government Regarding Decentralization on Managing Islands in The Borders Areatowards Indonesia the World Maritime Axis - Pailah, Steven Yohanes (AIBPM Publisher, 2021)
The authority of Local Government regarding on management islands in the border area requires access from the Central Government. The purpose of this research is to find a new concept of local government authority at the border. The methodology used is the normative juridical method. The results of the study: there is an overlapping authority of the Central Government and Local Government, limited access and authority of the Local Government to develop border areas, border development requires decentralization and the authority of the Local Government. In conclusion, the Central Government handed over the federative authority to the Local Government regarding the managing islands in the border areas, the budget for developing the potential of the border areas and the managing islands in the border areas towards the World Maritime Axis.